All Days 2009
DOI: 10.2118/122014-ms
|View full text |Cite
|
Sign up to set email alerts
|

SAGD Subcool Control with Smart Injection Wells

Abstract: Steam-Assisted Gravity Drainage (SAGD) is a widely used in situ recovery process for heavy oil and bitumen reservoirs. The performance of the SAGD process is tied with growth of the steam chamber which in turn depends on uniform steam delivery along well length and the underlying geology and fluid properties in the near wellbore region. If the reservoir has poor injectivity due to poor underlying geology oil production suffers. This can be avoided in by examining the interwell subcool. The subcool is the tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Weaver et al (2005) also looked at both the installation and application of permanent downhole optical pressure and distributed-temperature-sensing (DTS) gauges in a deepwater Gulf of Mexico environment where the temperatures (approximately 52 C) were not as high as those encountered in a typical SAGD process (approximately 250 C). Gotawala and Gates (2009) looked at the use of a PID feedback control to control inflow-control-valve settings to promote subcool to be within a specified value. They applied a stochastic model of shale distribution and examined two flow regions, near-well and above-well, to decouple the effects of heterogeneity.…”
Section: Reviewmentioning
confidence: 99%
“…Weaver et al (2005) also looked at both the installation and application of permanent downhole optical pressure and distributed-temperature-sensing (DTS) gauges in a deepwater Gulf of Mexico environment where the temperatures (approximately 52 C) were not as high as those encountered in a typical SAGD process (approximately 250 C). Gotawala and Gates (2009) looked at the use of a PID feedback control to control inflow-control-valve settings to promote subcool to be within a specified value. They applied a stochastic model of shale distribution and examined two flow regions, near-well and above-well, to decouple the effects of heterogeneity.…”
Section: Reviewmentioning
confidence: 99%
“…In practice, this phenomenon has been partially controlled by running an inner tubing string to the toe of the well, creating a second, independent steam injection point. With injection at the heel and the toe of the well, more HO-B is mobilized effectively, but a 'barbell' steam chamber develops, reflecting how this well design has little capability to control fluid injection into targeted regions between these two fixed points (Gotawala and Gates 2009). …”
Section: Theory Of Picd Usementioning
confidence: 99%
“…Therefore, unconventional techniques of oil recovery, such as thermal recovery of bitumen, have proved to be the most efficient. Thermal recovery techniques pertaining to heavy oil recovery can broadly be said to consist of two steps; the first involves heating the bitumen such that its viscosity falls from millions of cP to around 20 cP, thus mobilizing it and the second involves directing the mobile bitumen towards a production well (Gotawala et al (2009) and Gotawala et al (2012)). The most current and widely used technologies for the fluidization of bitumen are Cyclic Steam Stimulation (CSS) and Steam-Assisted Gravity Drainage (SAGD) (Butler (1994)), both of which use steam.…”
Section: Introductionmentioning
confidence: 99%
“…Although preliminary research and some field implementations have suggested that PID control based techniques is an improvement over the open loop manual control (Gotawala et al (2009) and Gotawala et al (2012)), there still remains the inability of PID controllers to handle constraints and calculate optimal control gains for the MV. The process of achieving the desired subcool by increasing T P through injection of superheated steam and mobilizing the bitumen has a high time constant (τ ).…”
Section: Introductionmentioning
confidence: 99%